Using simulation mannequins and actors in training for external post-mortem examinations -experiences from use in medical students and police officers. (January 2021) - Flössel, U.; Clas, S.; Willemer, M.; Sommer, M.; Poweleit, G.; Schulze, R.; Heide, S.; Erfurt, C.
Abstract: In the daily practice of external post-mortem examinations and dealing with surviving dependents, striking failures can be observed regularly, pointing to an increased demand for training of the various professional groups involved. In this study, the experience gained from using simulation mannequins and actors for post-mortem examination training in medical students and police officers are presented. Since 2017, a training station has been offered at the Medical Faculty of the Technical University of Dresden (Germany) for practicing examinations in death scene and establishing communication with grieving relatives. It is conducted in small groups of up to 5 people, both for medical students and for police officers and police recruits. These courses are evaluated by means of questionnaires including 3 and 11 items respectively for the different groups. The questionnaires have been completed by 679 medical students and 67 police participants. Both groups of participants evaluated their previous experience as average. They assessed the course as having a high degree of practical and professional relevance. The didactic transfer of the teaching contents and its competent support were rated remarkably positive by the participants. Additionally, the police group reported high rates of approval for the use of feedback, the learning effect, and the appropriateness of the group size. The establishment and continuation of the simulation-based external post-mortem examination in the form of small-group teaching is associated with a considerable expenditure of equipment, material and personnel. In addition, its implementation requires sound cooperation structures. On the other hand, introduction and continuation of these types of additional teaching and learning methods, with a large practical component, can increase confidence in daily practice, and thus improve the quality of external post-mortem examination. Ultimately, this can also improve the cooperation between forensic medicine and the investigating authorities. Highlights: Simulation-based post-mortem external examination training was carried out using dolls and actors. Evaluation by medical students and police officers showed positive results. This type of training can contribute to an increase in the quality of external examination of bodies in the death scene.